Merkel cells immunohistochemical study in striped dolphin (Stenella coeruleoalba) skin. (February 2019) - Lauriano, E.R.; Pergolizzi, S.; Aragona, M.; Spanò, N.; Guerrera, M.C.; Capillo, G.; Faggio, C.
Highlights: For the first time, the Merkel cells (MCs) have been characterized in the dolphin skin. Merkel cells (MCs) are specialized skin receptors. Merkel cells (MCs) participate in skin disorders through the release of neuropeptides and hormones. Abstract: Cetacean mechanical senses, such as hearing, echolocation, active touch and the perception of water movements, are essential for their survival. Dolphins skin possesses dense packing of dermal papillae associated with the cutaneous ridges that suggests a sensory function, furthermore they are well innervated and very sensitive to touch. This is mediated by mechanoreceptors, abundant in the region of the head and in the dorsal part of the body. Most odontocetes possess vibrissae (i.e., sensory hair) that have been well described in literature and present a microanatomy similar to that of terrestrial mammals. The aim of this study was to characterize Merkel cell through use of specific antibodies: Substance P, Anti-calbindin DK28, Anti-5HT, Leu- enkephalin, Protein Gene Product 9.5 (PGP9.5) and Anti-Human Neuronal Protein, for the first time. Merkel cells (MCs) in the dolphin skin are specialized skin receptors, characterized by their particular location and close association with nerve terminals. The presence of neuroendocrine markers and different neuropeptides confirms that MCs play also neuroendocrine function and are considered as part of the diffuse neuroendocrine system. Furthermore, the presence of Leu-enkephalin in Merkel cells could involve these cells in inflammatory responses in the skin.